PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERNAL, SISTEM INFORMASI AKUNTANSI, GOOD GOVERNANCE DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN (SKPD KABUPATEN PESAWARAN) - Hakiki, Candra; Luthfi, Muhammad; Puspita, Indah Lia (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2020)
This study aims to determine the effect of the variable Human Resources Competency, Utilization of Information Technology, Internal Control Systems, Accounting Information Systems, good governance and Organizational Commitment to the quality of financial statements in the SKPD Pesawaran District. The data collection method uses primary data, the population in this study were 100 people from 20 SKPD, with a sample of 40 respondents. Based on the results of data processing using multiple linear regression methods with SPSS software, it is proven that the variable Human Resource Competency, Internal Control Systems, Good Governance, Organizational Commitment have a significant effect on the Quality of Financial Statements. But the variable Utilization of Information Technology and Accounting Information Systems has no effect on the quality of financial statements in the Pesawaran District SKPD.  Keywords: Human Resources Competency, Utilization of Information Technology, Internal Control Systems, Accounting Information Systems, Good Governance, Organizational Commitment, Quality of Financial Statements.